ANALISIS HUKUM ISLAM DAN PERDA KOTA SURABAYA NO. 1 TAHUN 1997 TERHADAP ALIH SEWA TANAH SURAT IJO - Nadliyatul Mufidah (Maliyah : Jurnal Hukum Bisnis Islam, 2016)
Land and home is the most important necessity in everyone's life, in everyday life to meet the needs of the home as a residence for some people who do not have homes to meet these needs by leasing land owned by others for building his house. Lease is an agreement on something expediency containing specific purpose and permissible and receive a replacement or substitute with a particular skill, then it should be done under the provisions of shara '. However, the practice of lease made public Ambengan Batu Tambaksari Surabaya contrary to the argument and the terms of the lease. Results of this study concluded that there are fundamental similarities between Islamic law and regulation of Surabaya city No. 1 of 1997 on the practice Surat Ijo over the land lease is allowed to conduct transactions over the lease as long as it in accordance with the agreed terms. In addition there is a difference between Islamic law and regulation of Surabaya No. 1 of 1997 that the lease will end if the fulfillment of benefits that expiration of a predetermined. While in Surabaya City Regulation No. 1 of 1997 says that the land use permit Surat Ijo may be terminated if the land will be used for the benefit of the region and the land must be immediately vacated. So that the rights of lease will automatically come to an end even though there is still time permits.